تحليل شبكة PERT باستخدام تقديرات نظرية المجموعات الضبابية (دراسة حالة) - حجير, سمير موسى; الرفاعي, عبد الهادي; الصرن, غزوة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تلائم نظرية المجموعات الضبابية حالة نقص المعلومات وضبابيتها، التي تحد من القدرة على استخدام الطرائق الإحصائية في تقدير زمن تنفيذ أنشطة المشروع، فضلاَ عن إهمال تلك الطرائق للعوامل النوعية المؤثرة على عامل الزمن، كما تمّكن هذه النظرية من تحويل العبارات اللغوية التي يستخدمها الخبراء في تقديراتهم إلى مقادير كمية ومقاييس رياضية. يتجلى هدف البحث في تحليل شبكة PERT (أسلوب تقييم ومراجعة البرنامج) باستخدام المؤشرات المعدلة لتابع التوزيع الاحتمالي الخاضع له زمن النشاط، وذلك بعد إدخال تأثير العوامل النوعية عليها باستخدام نظرية المجموعات الضبابية، ومقارنته مع التحليل التقليدي لشبكة PERT الموضح عليها أنشطة مرحلة الإعداد والتجهيز لرحلة بحرية هادفة إلى نقل 3000 طن بالات مواد خام . أشارت نتائج الدراسة إلى صحة فرض البحث الأساسي بأن تقديرات نظرية المجموعات الضبابية جيدة أكثر من تقديرات النظرية الاحتمالية، حيث كان زمن تنفيذ المشروع المقدر بالطريقة الضبابية أقرب إلى زمن تنفيذه الفعلي. Fuzzy Sets Theory is convenient for analysis of incomplete and fuzzy information, which limits statistical ability to estimate activity duration. Besides, this theory's methods ignore the qualitative factors affecting the time of project completion. Moreover, the theory makes it possible to transform the linguistic terms used by experts into mathematical figures The study seeks to analyze PERT (Program Evaluation and Review Technique) Network using modified parameters of probability distribution, to which project duration is subject. This is done by introducing the effect of qualitative factors through Fuzzy Sets Theory and comparing it with the traditional analysis of PERT network, which explains the steps of preparation for shipment of 3000 tons of raw material. Results support the basic hypothesis of this study, which is that estimations of Fuzzy Sets Theory are better than those of the Theory of Probability, since estimated time of completion of the project by fuzzy method is closer to the time of actual completion.